2019
DOI: 10.1126/scisignal.aao7194
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-dependent B cell activation by fucose-binding bacterial lectins

Abstract: Bacterial lectins are typically multivalent and bind noncovalently to specific carbohydrates on host tissues to facilitate bacterial adhesion. Here, we analyzed the effects of two fucose-binding lectins, BambL from Burkholderia ambifaria and LecB from Pseudomonas aeruginosa, on specific signaling pathways in B cells. We found that these bacterial lectins induced B cell activation, which, in vitro, was dependent on the cell surface expression of the B cell antigen receptor (BCR) and its co-receptor CD19, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 110 publications
4
27
3
1
Order By: Relevance
“…Although in that study we did not measure DSA, it is interesting to speculate that Pseudomonas aeruginosa‐ mediated neutrophil B7 upregulation could bolster CD28‐mediated CD4 + T cell help to B cells to promote DSA generation in a similar manner. Ultimately, the inflammatory environment induced by Pseudomonas aeruginosa may promote the clonal expansion of alloreactive T cells and the polyclonal activation of B cells, and upregulation of HLA molecules on airway epithelial cells to amplify the humoral alloimmune response. Pseudomonas aeruginosa is also capable of facilitating affinity maturation and promoting isotype switching and somatic mutations in alloreactive B cells, especially if these antigens are already exposed on the allograft .…”
Section: Discussionmentioning
confidence: 99%
“…Although in that study we did not measure DSA, it is interesting to speculate that Pseudomonas aeruginosa‐ mediated neutrophil B7 upregulation could bolster CD28‐mediated CD4 + T cell help to B cells to promote DSA generation in a similar manner. Ultimately, the inflammatory environment induced by Pseudomonas aeruginosa may promote the clonal expansion of alloreactive T cells and the polyclonal activation of B cells, and upregulation of HLA molecules on airway epithelial cells to amplify the humoral alloimmune response. Pseudomonas aeruginosa is also capable of facilitating affinity maturation and promoting isotype switching and somatic mutations in alloreactive B cells, especially if these antigens are already exposed on the allograft .…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in biofilm formation and bacterial adhesion, LecB was also shown to carbohydrate-dependently block human ciliary beating, 25 interfere with tissue repair processes 26 and, recently, activate B-cells. 27 Furthermore, a direct involvement of LecA and LecB in infection and host colonization by P. aeruginosa using a murine infection model revealed the suitability of both lectins as therapeutic targets. 28,29 Inhalation of an aerosol of fucose and galactose, the ligands of LecB and LecA, resulted in a reduction of bacterial load in human infected airways 30,31 and in mice.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Further, both lectins also play roles in the direct infection process: LecB conveys virulence through carbohydrate-dependent inhibition of human ciliary beating, 20 interference with repair of wounded tissues, 21 , 22 and activation of B-cells. 23 Next to its biofilm-related roles, it was shown that the d -galactose-binding LecA triggers host cell signaling pathways 24 and mediates membrane invaginations after binding to its cellular receptor, the glycosphingolipid Gb3. 25 In vivo , both proteins are involved in the P. aeruginosa infection process and host colonization in a murine infection model.…”
Section: Introductionmentioning
confidence: 99%